Getting Life Expectancy Estimates Right for Pension Policy - Ayuso, Mercedes (2018)
Ayuso, M., Bravo, J., & Holzmann, R. (2018). Getting Life Expectancy Estimates Right for Pension Policy: Period versus Cohort Approach. (pp. 1-30). (CESifo Working Papers; No. 7349). Munich Society for the Promotion of Economic Research ‐ CESifo GmbH.